Firm-specific Determinants of Aggressive Tax Management among East African Firms - Kimea , Alfred James; Mkhize, Msizi; Maama, Haruna (International Journal of Economics and Financial Issues, 2023)
Since tax represents an inflow of revenue to the government and an outflow of revenue to firms, factors that influence the tax planning activities of firms have gained considerable attention among management, shareholders, policymakers and researchers. Following the impact of taxation on an economy and a firm, the study investigated the factors that influence aggressive tax management practices of firms listed in East African economies. Data were collected from 99 firms for an 11-year period, from 2008 to 2018. Both cash effective tax rate and accounting effective rate were used as measures of tax planning. Multiple regression models were used for the estimation. The study results showed that smaller firms are more tax aggressive compared with larger firms, which is consistent with the political cost theory. This finding may alert policymakers and regulatory authorities (for example, revenue authorities) that small firms are most likely to avoid paying taxes compared with larger firms. This might be associated with fewer regulations and enforcements imposed on this category of business. The evidence further demonstrated that profitable firms are less tax aggressive. Consistent with the political power theory, this study has confirmed the view that profitable firms have enough earnings to pay their taxes and thus are less tax aggressive. The study further found that older firms are less involved in tax avoidance. This study has policy implications as it will assist both policymakers and firm management in their decision-making. Shareholders and firm management would benefit by understanding why some firms successfully reduce their tax burden compared to other firms.